2011
DOI: 10.1136/adc.2011.212563.34
|View full text |Cite
|
Sign up to set email alerts
|

Synbiotics for inflammatory bowel disease: useful in adults but problematic in paediatrics

Abstract: Introduction An altered colonic microbiota contributes to inflammatory bowel disease (IBD) pathogenesis. Adult studies suggest modification of the microbiota by synbiotics (probiotics+prebiotics) can improve ulcerative colitis (UC)1 and Crohn's disease (CD)2. Aim To assess the feasibility of using a synbiotic in children with IBD. Methods Patients with IBD aged 6 to 16 years were approached. Children were excluded if they used any prebiotic/probiotic agent in the preceding 14 days, were using antibiotics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Also, B longum + synergy 1 (OF‐IN) determined a significant decrease in clinical and histological activity, as well as in mucosal TNF‐α levels vs placebo 188 . These last results were not confirmed in children with IBD (CD, UC, and IBDU); moreover, PRE were poorly tolerated 189 …”
Section: Altered Microbiota: How Could We Manipulate It?mentioning
confidence: 99%
“…Also, B longum + synergy 1 (OF‐IN) determined a significant decrease in clinical and histological activity, as well as in mucosal TNF‐α levels vs placebo 188 . These last results were not confirmed in children with IBD (CD, UC, and IBDU); moreover, PRE were poorly tolerated 189 …”
Section: Altered Microbiota: How Could We Manipulate It?mentioning
confidence: 99%
“…In a randomized, double-blind, placebo-controlled trial in 18 patients with UC, Furrie et al [74] found that the use of a synbiotic consisting of B. longum and oligofructose-enriched inulin helps to reduce both macroscopic lesions assessed in sigmoidoscopy and microskopic inflammatory lesions assessed during histopathological examination of the rectal mucosa biopsy, while reducing the level of pro-inflammatory cytokines, like TNF-α and IL-1β. Those findings have not been confirmed by Hansen et al [75] in a study among children with IBD. In a prospective multicenter, randomized study Chermesh et al [76] showed that treatment with a mixture of four probiotic species and four prebiotics had no beneficial effect on postoperative recurrence in 30 enrolled patients with CD.…”
Section: Synbiotics In Inflammatory Bowel Diseasesmentioning
confidence: 57%
“…A meta-analysis assessing the efficacy of synbiotics in UC revealed encouraging results about the safety and efficacy of synbiotics as a therapeutic option for UC ( 126 ). However, the beneficial effects of synbiotics are questionable in pediatric IBD cohorts and in patients with CD, due to reports of poor efficacy and tolerability ( 58 ).…”
Section: Dietary Interventions In Gastrointestinal Diseasementioning
confidence: 99%